1999
DOI: 10.1021/bi982728m
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Conformational Changes in the Crystal Structures ofPneumocystis cariniiDihydrofolate Reductase Complexes with Folate and NADP+,

Abstract: Structural data from two independent crystal forms (P212121 and P21) of the folate (FA) binary complex and from the ternary complex with the oxidized coenzyme, NADP+, and recombinant Pneumocystis carinii dihydrofolate reductase (pcDHFR) refined to an average of 2.15 A resolution, show the first evidence of ligand-induced conformational changes in the structure of pcDHFR. These data are also compared with the crystal structure of the ternary complex of methotrexate (MTX) with NADPH and pcDHFR in the monoclinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
81
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 21 publications
23
81
2
Order By: Relevance
“…For example, the N23S protein, a variant with kinetic properties very similar to wild type, is in loop 23 in pcDHFR (loop 20 in Escherichia coli), the loop that opens and closes over NADPH during the catalytic cycle (16). Likewise position 31 sits near the substrate binding site, but substitution of phenylalanine for serine at that site produced only modest effects on the K m values for substrate and cofactor while producing statistically significant resistance to both trimethoprim and OAAG324.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the N23S protein, a variant with kinetic properties very similar to wild type, is in loop 23 in pcDHFR (loop 20 in Escherichia coli), the loop that opens and closes over NADPH during the catalytic cycle (16). Likewise position 31 sits near the substrate binding site, but substitution of phenylalanine for serine at that site produced only modest effects on the K m values for substrate and cofactor while producing statistically significant resistance to both trimethoprim and OAAG324.…”
Section: Resultsmentioning
confidence: 99%
“…The deduced structure of P. jirovecii DHFR was calculated by homology modeling to the crystal structure of the P. carinii DHFR ternary complex with methotrexate and NADPH (15)(16)(17). The homology data for the pjDHFR complex with OAAG324 ( Fig.…”
Section: Fig 1 Schematics Of the Pjdhfr Inhibitors Trimethoprim And Omentioning
confidence: 99%
“…The loop on one side of the site extends from residues 20 to 33, partially encompassing helix A, and is believed to contain regulatory elements for binding in some bacterial species (19,44). The largest differences are seen at residues 21 to 25, with shifts in the main chain conformation of Ͼ1 Å relative to the MTX complex (see Fig.…”
Section: Structure Of B Anthracis Dhfr-rab1 Complexmentioning
confidence: 99%
“…Since immunosuppressed patients and those with AIDS are severly affected by these pathogens, efforts have been focused on the design of antifolates that are selective against P. carinii DHFR (pc DHFR) and T. gondii (or tgDHFR) (12, 18, 22-24, 27, 28, 33, 42, 44, 48). In most of these studies, antifolate selectivity reported as a ratio of 50% inhibitory concentrations (IC 50 s) from two DHFR species was measured against crude DHFR preparations from rat liver (44,47,48).Evidence from sequence analysis and three-dimensional crystal structures of DHFR from many species shows that there is a high degree of conservation at the primary sequence and structural level among DHFRs (8,[10][11][12][13][14]17,19,29,34,36,37,41,43,50,53,55). However, kinetic and biochemical characterization data reveal differences in the mechanism of action that result in significant species specificity by selected inhibitors (15-17, 21, 25, 26, 31, 36, 39, 43).…”
mentioning
confidence: 99%
“…Evidence from sequence analysis and three-dimensional crystal structures of DHFR from many species shows that there is a high degree of conservation at the primary sequence and structural level among DHFRs (8,[10][11][12][13][14]17,19,29,34,36,37,41,43,50,53,55). However, kinetic and biochemical characterization data reveal differences in the mechanism of action that result in significant species specificity by selected inhibitors (15-17, 21, 25, 26, 31, 36, 39, 43).…”
mentioning
confidence: 99%